The development of small enterprises during and after crisis: Comparative analysis of Greece and Poland - Simeon Karafolas; Maciej Woźniak (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2020)
Purpose: The purpose of the paper is to offer a comparative analysis of the development of small enterprises in Greece and Poland in the period just after global financial crisis which turned into an economic and social crisis for some countries, as the Greek example. The paper aims to discuss differences and similarities of small enterprises in two countries that suffered to a different level of the economic crisis. Design/methodology/approach: The authors decided to adopt three quantitative measures determining the degree of development of these companies: the number of active enterprises, the number of employees and the contribution to the Gross Domestic Product (GDP). The above measures were analyzed against the background of changes in the economic growth rate. Findings: Both countries were affected by the economic crisis but to a different level. Especially Greek economy suffered from the consequences of the austerity policy applied as a consequence of the agreement to obtain the international financial support. Poland on the contrary did not have to apply such an austerity program. Crisis consequences had severe consequences on the economy and negative effects on the GDP of these countries. Research limitations/implications: It should be noted that the presented results are based on quantitative methods, while the economic development also covers qualitative issues. Nevertheless, the analysis of data suggests the existence of a relationship between the adopted measures of small enterprises development and the value of GDP. Therefore, it indicates the need for further research, using more advanced methods of analysis. It is also worth expanding the research using qualitative methods. Originality/value: The paper contributes to the market failure theory in the area of macroeconomic business cycles. As the downswings because of crises influence on activity of enterprises, there is a need of appropriate government intervention. The analyzed examples suggest that higher level of monetary and credit policy in Poland seems to have a positive impact on the development of small enterprises in the analyzed space time. On the contrary, the austerity program in Greece might negatively affect the small companies.
Keywords: L16; L22; G01; 330; Small enterprises; Economic crisis; Greece; Poland